2021
DOI: 10.1126/sciadv.abc7982
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees behave prosocially in a group-specific manner

Abstract: Chimpanzees act cooperatively in the wild, but whether they afford benefits to others, and whether their tendency to act prosocially varies across communities, is unclear. Here, we show that chimpanzees from neighboring communities provide valuable resources to group members at personal cost, and that the magnitude of their prosocial behavior is group specific. Provided with a resource-donation experiment allowing free (partner) choice, we observed an increase in prosocial acts across the study period in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 64 publications
1
42
1
2
Order By: Relevance
“…cotton-top tamarins ( Cronin et al, 2009 ; Stevens, 2010 ), meerkats ( Amici et al, 2017 ), carrion crows and azure-winged magpies ( Horn et al, 2021 )), while others also found prosociality in independently breeding species ( e.g . cichlids ( Satoh et al, 2021 ), long-tailed macaques ( Massen et al, 2010 ), capuchin monkeys ( Lakshminarayanan & Santos, 2008 ), chimpanzees ( Warneken & Tomasello, 2006 ; Melis et al, 2011 ; van Leeuwen et al, 2021 ), bonobos ( Tan & Hare, 2013 ; Tan, Ariely & Hare, 2017 ; Krupenye, Tan & Hare, 2018 ). This suggests that cooperative breeding is not a prerequisite for prosocial behaviour ( Cronin, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cotton-top tamarins ( Cronin et al, 2009 ; Stevens, 2010 ), meerkats ( Amici et al, 2017 ), carrion crows and azure-winged magpies ( Horn et al, 2021 )), while others also found prosociality in independently breeding species ( e.g . cichlids ( Satoh et al, 2021 ), long-tailed macaques ( Massen et al, 2010 ), capuchin monkeys ( Lakshminarayanan & Santos, 2008 ), chimpanzees ( Warneken & Tomasello, 2006 ; Melis et al, 2011 ; van Leeuwen et al, 2021 ), bonobos ( Tan & Hare, 2013 ; Tan, Ariely & Hare, 2017 ; Krupenye, Tan & Hare, 2018 ). This suggests that cooperative breeding is not a prerequisite for prosocial behaviour ( Cronin, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PCT has been suggested to be cognitively too demanding ( Burkart & Rueth, 2013 ; Claidière et al, 2015 ; Tan, Kwetuenda & Hare, 2015 ; Melis, 2018 ). Therefore, an alternative version has been proposed: the group service paradigm (GSP) ( Cronin, Schroeder & Snowdon, 2010 ; Burkart & van Schaik, 2013 ; Burkart et al, 2014 ; House et al, 2014 ; van Leeuwen et al, 2021 ). In this costly version of the PCT, subjects can choose whether to deliver food only to a partner or to provide no food at all, which has also been referred to as a single-choice (go) task ( Jensen, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…This result contradicts our main hypothesis that the crows and magpies would behave prosocially towards their group members, as has been observed in the wild [ 31 , 32 ] and demonstrated experimentally in captive birds in the group service paradigm for both species [ 45 , 55 ] and in a naturalistic food provisioning experiment with azure-winged magpies [ 39 ]. Given that prosocial behavior has been shown to depend on the context and/or on the specific group, when tested in other non-human animals (e.g., chimpanzees [ 11 , 61 , 62 ]), it is possible that the subjects were not motivated to act prosocially in the context of the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Simple experimental setups, such as the group service paradigm, which do not require individuals to be separated from the group, and where behavioral contingencies are obvious to the birds, are an equally promising avenue for the investigation of prosocial behavior [ 45 , 55 ]. Both paradigms can be easily adapted to other bird species or other non-human animal taxa (e.g., primates [ 3 , 4 , 10 , 11 ]) and could even be adapted to testing individuals in the wild (for an example of using the group service paradigm on corvids living in the wild, see [ 45 ]). In conclusion, while the current study fails to show prosocial tendencies in carrion crows and azure-winged magpies, when tested in a token transfer paradigm, our findings highlight the strong impact of methodology on whether animals are able to exhibit prosocial tendencies, as well as the importance of using valid comparative methods and systematic replications across different species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation